(untitled) (Archive of Conferences, 2021)
The article reflects the model of developing the general cultural competence of teachers working in the public education system. The analysis also shows the axiological-motivational, conceptual, technological, reflexive and creative levels of development of general cultural competence of teachers working in the public education system, as well as the internal components of communicative competence